The Importance of Pendidikan Profesi Guru (PPG) in Improving the Quality of Education in Indonesia - Ardana, Lydia; Yuniati, Suci; Kurniati, Annisah; Rahmi, Depriwana (PPG IKIP Siliwangi, 2025)
To raise the standard of education in Indonesia, Pendidikan Profesi Guru (PPG) is a crucial advanced curriculum. PPG bridges the gap between academic theory and practical field experience to equip aspiring teachers with the necessary skills and knowledge. The goals of this project are to identify strategies for enhancing teacher professionalism through the PPG program and to assess its impact on educational quality. As part of this study approach, secondary data from earlier studies on PPG's efficacy in raising academic standards and teacher professionalism are analyzed. Through an innovative curriculum, extensive field practice, ongoing training, the development of ethical principles, and systematic performance evaluation, PPG can enhance teacher professionalism, according to the research findings. With the correct assistance, PPG develops into a solid basis for producing teachers who are capable, committed, and professional. To achieve Indonesia's goal of high-quality education, PPG is crucial, playing a significant role in equipping teachers with the knowledge and skills they need.